A coupled thermal-elastic-plastic-damage model for concrete subjected to dynamic loading. (June 2022) - Ma, Jianjun; Chen, Junjie; Chen, Wanxiang; Huang, Linchong
Highlights: Thermal-plasticity-damage can be captured within a consistent and unified manner. A more general equation of state in semi-logarithm space is proposed. New hardening rules have been proposed through a unified consistent condition. A new damage evolution law has been presented in this paper. A temperature reduction function is proposed for brittle-ductile transition. Abstract: A coupled thermal-elastic-plastic-damage model for concrete subjected to dynamic loading is proposed. This model is formulated in the thermodynamic framework, with the adoption of critical state concept, bounding surface plasticity and continuum damage model (small strain being assumed). The contributions of temperature change, plasticity hardening/softening, damage evolution have been taken into account, with cross coupling effects among temperature, damage, strain rate and plasticity being considered through the consistent condition of thermodynamic model. Specifically, the variation of dynamic yield surface depends on the level of mean pressure, damage evolution, strain rate and plastic strain, which can be expressed through a general hardening law in bounding surface plasticity. The extension or contraction of dynamic bounding surface has been described by both compression and extension parts. For the consideration of higher strain rates and ultimately high pressures, the relationship between volumetric strain-mean pressure has been expressed through a more general equation of state (GEOS), which is different from traditional equation of state (EOS) under impact loading. This model has been validated through modelling extensive experimental results in literature, with good agreement among modelling results and experimental data being achieved. All model parameters are measurable physical entities and can be calibrated through conventional experimental approach or taken from literature.